Pengaruh Orientasi Kewirausahaan, Orientasi Pasar dan Orientasi Pembelajaran terhadap Inovasi Produk (Studi pada Pengusaha Kecil di Kota Palembang) - Lisnini, Rini; Maretha, Fetty; Pebrianti, Yulia (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT This study aims to determine the effect of entrepreneurship orientation, market orientation and learning orientation to product innovation. The population in this research is female small business actors in the field of food processing in Palembang City. The sample in this study amounted to 150 people spread in seven sub-districts in Palembang. Sample determination technique used in this research is purposive sampling. The analysis method used in this research is linear regression analysis. The results of the study explain that entrepreneurship orientation variables have no significant effect on product innovation. Market orientation variables significantly influence product innovation. Learning orientation variables significantly influence product innovation.